Growth performance and gonad development in Diploid and Triploid Clarias batrachus (Linnaeus) - Siraj, Siti Shapor; Daud, Siti Khalijah; Ang, Kong Nian (Universiti Putra Malaysia Press, 1993)
Full siblings of diploid and triploid walking catfish, Clarias batrachus, were reared in rectangular fibreglass tanks starting at the age of three weeks. Growth performances of diploids and triploids were compared by feeding with a 30% protein diet. At the end of the study period growth rate was found to be insignificantly different (P>0.05) between the diploid and the triploid. However, triploid fish had poorly developed gonads. Triploid ovaries contained fewer primary oocytes with some abnormal maturing oocytes. Triploid testes contained fewer seminiferous tubules and a larger amount of connective tissue.